1980
DOI: 10.1002/j.1556-6978.1980.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The Doctoral Comprehensive Examination in Counselor Education

Abstract: According to recent survey results, the doctoral comprehensive examination is still the most often used method of evaluating doctoral students for candidacy. Widespread dissatisfaction, however, on the part of both professors and students continues. This article gives suggestions for improving the written portion of the doctoral comprehensive examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Scholars' primary recommendation for future research with respect to the comprehensive examination has been to identify and clarify the purpose of the exam (Peterson et al, 1992;Thomason et al, 1980). A lack of consensus about purpose often leads to an interpretation that comprehensive exams are a rite of passage (Tinker & Jackson, 2004).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Scholars' primary recommendation for future research with respect to the comprehensive examination has been to identify and clarify the purpose of the exam (Peterson et al, 1992;Thomason et al, 1980). A lack of consensus about purpose often leads to an interpretation that comprehensive exams are a rite of passage (Tinker & Jackson, 2004).…”
mentioning
confidence: 99%
“…As a milestone in a students' progression towards their degree, Thomason et al (1980) acknowledged a need to study the comprehensive examination in doctoral level counseling programs. Although exams may serve multiple purposes, Thomason et al (1980) found the ultimate goal of the comprehensive exam was not clear.…”
mentioning
confidence: 99%
See 3 more Smart Citations